Global trade in the premodern world - Smith, Richard L. (Richard Lee), 1945- author aut Link Link Link
1 online resource
Keywords: "Global Trade in the Premodern World offers an authoritative and expansive history of exchange and interaction across Eurasia from the prehistoric origins of trade to the integration of large parts of this world-system by the fifteenth century CE. The book tackles questions that are critical to our understanding of premodern globalization. How did global trade in the premodern world take shape? Who did the trading and what motivated them? Which commodities were traded and how did different goods influence how trading networks functioned? How did geography change how and where people carried goods? How did states and communities seek to control the practice of commerce? And finally, what was the impact of trade on political structures and in the relationship between different states, empires, and communities? Drawing on the fruits of research in history, anthropology, and archaeology, as well as primary sources produced by authors from Africa, Asia and Europe, Global Trade in the Premodern World is a book of remarkable scope written engagingly and accessibly with scholars, students, and non-specialists in mind"-- Provided by publisher.